On the value of silence: A comparison of stated and revealed preferences for the external costs of traffic noise - Erichsen, Emil; Bjørner, Thomas Bue (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
During the last decades several studies have been carried out in order to measure the external costs of traffic noise. Both direct valuation methods, like contingent valuation (CV) and revealed preference studies linking noise levels to house prices, have been used. Though comparison of results from such studies are common, only few studies have carried out such a comparison based on the exact same area/respondents. We present preliminary results from an ongoing research project, which compares valuation results obtained by the CV method and hedonic pricing for residents in urban Copenhagen. The contingent valuation study is carried out by combining a standard socio-acoustic survey on noise annoyance with a CV scenario on the removal of the noise annoyance. Data from the hedonic pricing are partly obtained from survey and partly from the Danish housing register.